Analysis of anticipation by 3D motion capturing - a new method presented in karate kumite - Petri, K.; Lichtenstein, M.; Bandow, N.; Campe, S.; Wechselberger, M.; Sprenger, D.; Kaczmarek, F.; Emmermacher, P.; Witte, K. (Journal of Sports Sciences, 2017)
Anticipation is an important performance factor in karate kumite. A new approach analysing anticipation in realistic combat situations by motion capturing with a high temporal resolution is presented. The advantage of this approach is that both karate athletes interacting sports specific can be recorded synchronously; thus, the presented method has the potential to analyse visual information pickup due to coordination pattern of interaction between real athletes. The aim is to demonstrate the usability of the current method for anticipation research and to investigate if the distance between two athletes and their attacking technique play a role in the reaction of the defending athlete. Furthermore, relevant cues lying within each attacking technique and little individual differences are shown. Four male karate athletes took part in this study. Logistic regression indicated that both factors (distance × attacking technique) play a significant role in reaction. However, a correlation between these factors shows that only the attacking technique is a good predictor for reaction. Results show that the attacking technique jabbing punch (jap. Kizami-Zuki) was easier to anticipate than the attacking techniques reverse punch (jap. Gyaku-Zuki) and the round kick (jap. Mawashi-Geri).